Effectiveness Of Repair Method Using Hybrid Fiber Reinforced Polymer Fabric On Concrete-Filled Double Skin Steel Tubular Columns Exposed To Fire - Zuki, Sharifah Salwa Mohd (2017)
Concrete-filled double skin steel tubular (CFDST) column is becoming more popular nowadays due to its superior performance compared to conventional composite column and concrete-filled steel tubular (CFST) column. However, the use of this type of column is still limited to outdoor construction such as bridge piers and transmission tower where fire is not a main concern. Moreover, existing research studies on CFDST column only focused on fire performance and limited research studies can be found on residual strength of the CFDST column. Residual strength can be used to determine the most suitable repair method needed in order to retrofit the column. Therefore, this study aims to study the effect of different parameter towards residual strength of CFDST column. Among discussed parameter is thickness of outer steel tube ( ) and fire exposure time. In addition, this study is also aim to determine the effectiveness of repair method using Single and Hybrid fiber reinforced polymer (FRP) of fire-damaged CFDST columns. CFDST columns were heated in accordance of ASTM E119-11: Standard Test Methods for Fire Tests of Building Construction and Materials until the temperature reached 600°C. Afterwards, the temperature was kept constant for two different durations, i.e., 60 minutes and 90 minutes. The specimen was then left to cool down to room temperature inside the furnace before it was taken out and repaired by Single and Hybrid FRP. The specimens were categorized into the following three groups: (1) unheated or control specimens, (2) heated and unrepaired and (3) heated and repaired. All specimens were subjected to axial compression loading until failure. The first and second category specimens failed by local outward buckling of outer steel tube, crushing of concrete and local buckling of inner steel tube; whereas, specimens in third category failed by rupture of FRP followed by similar local buckling and concrete crushing as those observed in first and second category specimens. Ultimate strength, secant stiffness and Ductility Index (DI) decreased as temperature of the specimen increased. The lost in secant stiffness of thinner CFDST specimens exposed to 60 minutes of fire exposure time is similar to thicker CFDST specimens exposed to 90 minutes of fire exposure time regardless of its diameter. In addition, CFDST specimens exposed to 90 minutes of fire exposure time were more ductile than control specimen. RSI and secant stiffness increased with the increased in fire exposure time. Interestingly, the highest RSI achieved is only 22% which means the specimens were still able to carry more than 70% of its initial load after being exposed to 90 minutes of fire exposure time with only 3 mm thickness of outer steel tube. Repairing the fire-damaged CFDST columns with Single and Hybrid FRP are proven to improve ultimate compressive strength significantly. The increment in ultimate compressive strength is more pronounced in specimen with Hybrid FRP and thinner outer steel tube. The secant stiffness and Ductility Index (DI) of repaired specimens were however not able to be restored to those of control specimen.